Thrombospondin binding by parasitized erythrocyte isolates in falciparum malaria. - Sherwood, J; Roberts, D; Marsh, K; Harvey, E; Spitalnik, S; Miller, L; Howard, R (1987)
Toward understanding the pathogenesis of vascular sequestration in falciparum malaria, we investigated binding of Plasmodium falciparum parasitized erythrocyte isolates to thrombospondin and other adhesive proteins. Blood samples with rings from 12 patients with falciparum malaria were cultured 30 hr until parasites were mature trophozoites and schizonts. All parasitized erythrocyte isolates bound to thrombospondin, but not to fibronectin, laminin, vitronectin, or factor VIII/von Willebrand factor. Parasitized erythrocyte binding varied among isolates, ranging from 192 to 6,725 per mm2, average 2,953. There was good correlation between trophozoite plus schizont % parasitemia and thrombospondin binding (r = 0.884, P less than 0.001). In two patients with stupor, 3,642 and 2,864 parasitized erythrocytes bound per mm2, in proportion to parasitemia, suggesting cerebral malaria is not due to increased binding affinity. These results indicate there is a conserved function among isolates from this geographic region, known to be antigenically diverse at the parasitized erythrocyte membrane surface. These results support the hypothesis that specific binding to an endothelial receptor, possibly involving thrombospondin, plays a role in vascular sequestration in falciparum malaria.